İskandinav Mimarlığında Estetik: Plastik ve Anlamsal Biçim Analizi - Işıkoğlu, Beyza Onur (Journal of History Culture and Art Research, 2019)
Aesthetic in Scandinavian Architecture: Analysis of Plastic and Semantic Form Abstract The concept of aesthetics is a relative concept which has a wide area in its subject and can vary according to society and time. The concept of aesthetics in architecture reflects the objective and semantic structure of architecture. This concept is also important for establishing a judicial system. In other words, it is a value system that determines format and content. Aesthetic criteria, when adopted by society, constitute a common taste and an understanding of art. This concept, which is also defined as social taste, also expresses a cultural value and the architectural aesthetic understanding of each society is shaped according to various factors and gains meaning. In this context, the concept and understanding of aesthetics are discussed through examples of Scandinavian architecture. For this reason, firstly the general character and social structure of the Scandinavian countries are introduced and traditional-modern architectural styles of these countries are discussed. Then, the plastic form analysis of Scandinavian aesthetics (mass-space effect, color, use of light, contrast effect, measure, scale and ratio, rhythm) and semantic form analysis (use of metaphors, social symbols and codes in architecture) were examined. Thus, the factors that create data for the aesthetics of Scandinavian architecture were determined and which formal and semantic factors were used in the aesthetic understanding adopted in Scandinavian architecture were determined. İskandinav Mimarlığında Estetik: Plastik ve Anlamsal Biçim Analizi Öz Estetik kavramı, konusu itibariyle geniş bir alana sahip, toplumdan topluma ve zamana göre değişebilen göreceli bir kavramdır. Mimarlıkta estetik kavramı ise, mimarlığın nesnel ve anlamsal yapısını yansıtmaktadır. Bu kavram, bir yargı sistemi oluşturması bakımından da önemlidir. Bir başka deyişle mimarlıkta estetik, biçim ve içeriği belirleyen bir değer sistemidir. Estetik kriterler, toplum tarafından benimsendiği zaman ortak bir zevki ve sanat anlayışını oluşturmaktadır. Toplumsal beğeni olarak da tanımlanan bu kavram, kültürel bir değeri de ifade etmektedir ve her toplumun mimari estetik anlayışı, çeşitli faktörlere göre biçimlenmekte ve anlam kazanmaktadır. Bu bağlamda çalışmada, estetik kavramı ve anlayışı İskandinav mimarisi örnekleri üzerinden tartışılmaktadır. Bu nedenle öncelikle İskandinav ülkelerinin genel karakteri, toplumsal yapısı tanıtılmış ve bu ülkelerin geleneksel-modern mimarlık üslupları ele alınmıştır. Daha sonra, İskandinav mimarlığı estetiğinin plastik biçim analizi (kütlesel doluluk-boşluk etkisi, renk, ışığın kullanımı, kontrast etkisi, ölçü, ölçek ve oran, ritim) ve anlamsal biçim analizi (mimaride metaforların, toplumsal simge ve kodların kullanımı) irdelenmiştir. Böylece İskandinav mimarisi estetiğine veri oluşturan faktörler saptanmıştır ve İskandinav mimarlığında benimsenmiş olan estetik anlayışında, hangi biçimsel ve anlamsal faktörlerin kullanıldığı belirlenmiştir.